The Principle of Sustainable Development in International Investment Law: A Study from Vietnamese Perspective - Tran Thang, Long; Pham, Anh Le Tram (UI Scholars Hub, 2025)
International investment significantly contributes to economic development by fostering hunger eradication, poverty reduction, job creation, and the introduction of new technologies and services. However, it also presents challenges, including resource degradation, environmental decline, waste generation, and human rights violations. This article emphasizes integrating sustainable development principles into international investment law to balance investor and host country interests while safeguarding the environment and human rights for long-term sustainability. In Vietnam, a nation increasingly integrated into the global economy, legal frameworks stipulate sustainable development principles for foreign-invested projects, aligning with international standards to protect the environment and people alongside economic and social progress. Despite these efforts, Vietnam’s regulations exhibit limitations and unpredictability, hindering effective responses to potential international investment disputes. This study examines Vietnam’s approach to these principles and its practical implementation toward achieving sustainable development goals through investment, using case studies and conceptual analysis of international investment agreements. The central research question explores how Vietnam can leverage international investment benefits while ensuring sustainable development. The article analyzes the interplay between sustainable development and investment promotion, identifies key principles in investment agreements, and highlights challenges for host countries like Vietnam in managing expropriation disputes tied to public interest criteria. Findings underscore the need to prioritize sustainable development in attracting investment, proposing legal enhancements to strengthen state remedies against investor violations, and minimizing expropriation lawsuits. By addressing these gaps, Vietnam can better enforce sustainable practices, balancing economic gains with environmental and human rights protections. The research advocates for refined legal provisions to enhance Vietnam’s capacity to resolve disputes and uphold sustainable development commitments, offering actionable recommendations to perfect its legal framework in this domain.